Interaction between PHB2 and Enterovirus A71 VP1 Induces Autophagy and Affects EV-A71 Infection - Weitao Su; Shan Huang; Huimin Zhu; Bao Zhang; Xianbo Wu (Viruses, 2020)
Enterovirus A71 (EV-A71) is a major pathogen that causes severe and fatal cases of hand-foot-and-mouth disease (HFMD). HFMD caused by EV-A71 seriously endangers children’s health. Although autophagy is an important antiviral defense mechanism, some viruses have evolved strategies to utilize autophagy to promote self-replication. EV-A71 can utilize autophagy vesicles as replication scaffolds, indicating that EV-A71 infection is closely related to its autophagy induction mechanism. VP1, a structural protein of EV-A71, has been reported to induce autophagy, but the underlying mechanism is still unclear. In this study, we found that the C-terminus (aa 251–297) of VP1 induces autophagy. Mass spectrometry analysis suggested that prohibitin 2 (PHB2) interacts with the C-terminus of the EV-A71 VP1 protein, and this was further verified by coimmunoprecipitation assays. After PHB2 knockdown, EV-A71 replication, viral particle release, and viral protein synthesis were reduced, and autophagy was inhibited. The results suggest that PHB2 interaction with VP1 is essential for induction of autophagy and the infectivity of EV-A71. Furthermore, we confirmed that EV-A71 induced complete autophagy that required autolysosomal acidification, thus affecting EV-A71 infection. In summary, this study revealed that the host protein PHB2 is involved in an autophagy mechanism during EV-A71 infection.